2014
DOI: 10.5545/sv-jme.2013.1349
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modelling of Sheet Metal Forming Considering Anisotropy and Young’s Modulus Evolution

Abstract: The paper focuses on the modelling of springback within a formed stainless steel sheet. The main subject of this work is the construction of a constitutive model which simultaneously considers sheet anisotropy, damage evolution, and stiffness degradation in material during forming. The developed model is based on the Gurson-Tvergaard-Needleman damage model, which is adequately extended by the implementation of the anisotropic Hill48 plasticity and Mori-Tanaka's approach to stiffness degradation. Considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the numerical program ABAQUS, a material's anisotropy can be described with Hill's yield criterion [17] and [20], as expressed in Eq. (2).…”
Section: • the Most Important Contribution To The Research Of Indentamentioning
confidence: 99%
See 1 more Smart Citation
“…In the numerical program ABAQUS, a material's anisotropy can be described with Hill's yield criterion [17] and [20], as expressed in Eq. (2).…”
Section: • the Most Important Contribution To The Research Of Indentamentioning
confidence: 99%
“…Decreasing the numerical model of the indentation test to one quarter only [20] requires double-sided axis-symmetry ( Fig. 4), which was used to shorten the computer calculation times.…”
Section: Model Mesh and Loadsmentioning
confidence: 99%
“…Nevertheless, it is not quite enough to understand the mechanical behavior of each layer individually given that the global behavior is also driven by the interaction between layers. Moreover, when very thin skins are considered, such as the ones on the micro-sandwich materials, the mechanical properties can change and new constitutive model parameters are needed to accurately describe the formability and springback phenomena, as claimed by Starman et al (2014). Luzin et al (2005) compare several experimental techniques to measure the Young Modulus of samples made from sub-millimeter thickness layers, and observed that the elastic properties can no longer be measured with conventional mechanical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Among the mechanisms, roughly grouped into micromechanical models (e.g. [3] to [6]), uncoupled models (e.g. [1] and [2]) and coupled phenomenological models (e. g. [1], [7] and [8]), the Lemaitre coupled phenomenological model, following the continuum damage mechanics (CDM) may be considered as most appropriate for direct and continuous material characterization.…”
Section: Introductionmentioning
confidence: 99%